2017
DOI: 10.1093/infdis/jiw492
|View full text |Cite
|
Sign up to set email alerts
|

Boosting Immune Responses Following Fractional-Dose Inactivated Poliovirus Vaccine: A Randomized, Controlled Trial

Abstract: ACTRN12615000305527.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 15 publications
2
7
0
1
Order By: Relevance
“…Emerging data from Israel indicate that the immune response elicited in the elderly, elicited by a single dose of Pfizer’s mRNA vaccine mediates a degree of protection against infection and transmission 24 , although the age and the fact of having received only a single dose in this time window imply less than optimal antibody levels. “Fractional” dose vaccination has proven beneficial in viral poverty diseases 25 , 26 further supporting the findings of this study.…”
Section: Discussionsupporting
confidence: 86%
“…Emerging data from Israel indicate that the immune response elicited in the elderly, elicited by a single dose of Pfizer’s mRNA vaccine mediates a degree of protection against infection and transmission 24 , although the age and the fact of having received only a single dose in this time window imply less than optimal antibody levels. “Fractional” dose vaccination has proven beneficial in viral poverty diseases 25 , 26 further supporting the findings of this study.…”
Section: Discussionsupporting
confidence: 86%
“…These studies suggest that intradermal fIPV has less ability to boost antibody levels than the regular intramuscular dose, especially when the baseline titers are already high. However, recent studies among adults in Cuba [ 23 ] and among OPV-primed children aged 10 to 12 years in Sri Lanka (O. Mach, WHO, personal communication) found that an fIPV dose was as effective as a full intramuscular dose in boosting both humoral and mucosal immunity among OPV-immunized individuals. This suggests that fIPV through the intradermal route is as effective as IPV administered intramuscularly in boosting individuals with no or lower baseline titers.…”
Section: Summary Of the Scientific Evidencementioning
confidence: 99%
“…One of the options is to reduce the antigen content of each dose by administering a fractional intradermal (ID) dose of 0.1 mL of IPV, instead of the standard dose of 0.5 mL delivered IM. A number of clinical studies have compared ID delivery of reduced doses of IPV to full-dose IM delivery with variable results depending on the vaccination regimen used [9], [10], [11], [12], [13], [14], [15], [16], [17], [19], [20], [21].…”
Section: Introductionmentioning
confidence: 99%